LEXEMES MEAN GOD IN AL-QUR’AN AND ARABIC GOSPEL: SEMANTIC ANALYSIS - Yuangga Kurnia Yahya (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2018)
This research aimed to understanding the concept of divinity in Arabic culture through lexemes mean God which are used in al-Qur’an dan Arabic Gospel. Lexeme is the smallest unit of meaning that formed word. From lexeme, words, phrases, clauses, and discourses are formed according Arabic’s concept of divinity. Formal objects of this research are the lexemes mean God in al-Qur’an and Arabic Gospels. All of data derived from al-Qur’an and the Four Gospels in New Testament. This research applied semantic approach, especially which talks about form and meaning, Brown-Yule’s text and co-text, and Sapir-Whorf Hypothesa in relation between culture and language. The method used in this research is distributional method which is the lexeme and word as the deciding device. This research is a qualitative research caused of nature of the data that found and the data collection of this research purely based on library research. The process of this research passed three stages, data provision, data analysis with semantic approach, and the presentation of analysis result. The result of this research indicates that lexeme Allāh that means God has been known by Arabic people before the birth of Islam and Christian. This lexeme means the name of the highest God in Arabic’s polytheism and estimated that it used since Fifth century BC. Arabic Christians used this lexeme as the translation of “God” and referred to The Only One God 500 years before Muhammad’s birth. The lexemes mean God in al-Qur’an are Allāh, Rabb, Ilāh, Dhamīr (Anā, Anta, Huwa, and Nahnu), and the names of Allah (shifātu’l Lāh wa asmāu’l Lāh). As for the lexemes mean God in Arabic Gospels are Allāh, Rabb, Ilāh, Āb father, Yasū’ Jesus, ar-Rūh al-Quds Holy Spirit, al-Ibn Son, as-Sayyid Lord, al-Mu’allim Master, al-Malik King, and Dhamīr (Anā, Anta, and Huwa). The lexeme Allāh, Rabb, and Ilāh are the similar lexemes found in both Holy Books, but these lexemes have some difference in word category, sintaxis function, and semantic role. Furthermore, other lexemes used in same purpose, that is presenting a more complete pictures and more familiar about their God.